Resources and population traits modulate the association patterns in the common bottlenose dolphin living nearby the Tiber River estuary (Mediterranean Sea) - Pace, Daniela Silvia; Ferri, Sara; Giacomini, Giancarlo; Di Marco, Chiara; Papale, Elena; Silvestri, Margherita; Pedrazzi, Giulia; Ventura, Daniele; Casoli, Edoardo; Ardizzone, Giandomenico (Frontiers in Marine Science, 2022)
Sociality and ecological drivers that can influence individual association patterns are infrequently considered in wildlife management, although they are essential aspects affecting animals’ responses to both human-related pressures and conservation strategies. In common bottlenose dolphins (Tursiops truncatus), sex-specific social dynamics and interactions with anthropogenic activities may affect grouping and induce changes in relationships between individuals. Out of a total of 347 individuals, we assessed the level of association among 68 bottlenose dolphins that have been sighted more than five times near the Roman coast (central Mediterranean Sea, Italy). The half-weight index (HWI) of dyadic associations, their network relations, and stability over time were investigated by using the SOCPROG software. Outcomes showed that females were more strongly associated than other individuals, with both preferred constant short-term associations and random long-term associations, possibly resulting in greater success in rearing young. Individuals interacting with the bottom trawl fishery showed weaker and short-term associations. Temporary disruption of individual associations during interaction with fishery and the relatively low number of females with calves participating in depredation seem to denote both the opportunistic nature of interactions with fishing vessels and the offspring-related protection strategy. The results show that the dolphins in this region maintain a complex but flexible social structure that varies with local biological requirements and is resilient to anthropogenic pressures.